2017
DOI: 10.1097/md.0000000000006033
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular function in chronic alcoholics by real-time three-dimensional echocardiography

Abstract: Chronic alcohol consumption may lead to progressive cardiac dysfunction. The aim of this study was to evaluate the feasibility of using real-time 3-dimensional echocardiography (3DE) on assessing left ventricular (LV) function in chronic alcoholics.We classified 92 male alcoholics into mild, moderate, and severe groups; 30 age-matched controls were also recruited. LV end-diastolic volume (LVEDV), LV end-systolic volume (LVESV), LV ejection fraction (LVEF), LV mass (LVM), LV mass index (LVMI), and systolic dyss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
7
1
Order By: Relevance
“…We obtained a C-SDI of 8.0 ± 3.4% in the control group, higher than previously published ranges, [25] though differences in design and methodology as well as the sample size, could explain the differences. We cannot compare our findings in CA with other reports, but equivalent results have been shown in alcohol induced cardiomyopathy with realtime 3D echocardiography, with increased SDI in addicts compared to controls [49].…”
Section: Dyssynchrony Indexcontrasting
confidence: 58%
“…We obtained a C-SDI of 8.0 ± 3.4% in the control group, higher than previously published ranges, [25] though differences in design and methodology as well as the sample size, could explain the differences. We cannot compare our findings in CA with other reports, but equivalent results have been shown in alcohol induced cardiomyopathy with realtime 3D echocardiography, with increased SDI in addicts compared to controls [49].…”
Section: Dyssynchrony Indexcontrasting
confidence: 58%
“…Some epidemiological studies have shown beneficial effect of low alcohol consumption [6][7][8][9][10][11][12][13]. Although low alcohol consumption has some beneficial effects, the number of investigations of side effects of alcohol consumption commonly increase, as in our study [6][7][8][9][10][11][12][13]. Alcoholic cardiomyopathy (CMP) is defined as enlarged cardiac chambers with largely hypertrophy and extracellular matrix (ECM) remodeling [1].…”
Section: Discussionmentioning
confidence: 98%
“…Except for LA dimensions, these findings are consistent with our observations regarding the left ventricular ejection fraction. Therefore, diastolic dysfunction associated with alcohol use carries clinical significance as an initial sign of the CMP process [1,9,17,20]. It should also be borne in mind that other factors may have a predictive role in the development of alcoholic cardiac disease and these include the duration, frequency, and amount of alcohol consumption, the type of alcohol consumed, presence of additional substance abuse (cigarette, marihuana), and family history of cardiomyopathy [3,4,12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68%) followed by alcohol consumption between 5 to 8 years of age group (i.e. 32%) (Wang et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%